Exclusión social y las conductas disruptivas en los adolescentes de la Unidad Educativa San Carlos, año 2019 - Alarcon Lopez, Walter Wenceslao (2019)
The importance that is felt with the reality of social exclusion, which determines in a process, beyond the complex and the conviction of seeking an attempt to raise awareness, to face this serious and dramatic episode that addresses social exclusion. The globalized situation of a competitive society, is the primary value, the mechanisms of defense of exclusion constitute rules of play very elementary and necessary by the exclusionary nature, being thus, that children, adolescents, adults and why not say of emigrant elders, disabled, etc. Become easily excluded. In the political or private sphere, this phenomenon of social exclusion automatically lies in a questioning according to the society we have, because of poverty and extreme poverty, thus becoming an economically bad society, politically corrupt and socially dangerous and explosive. When we interpret social exclusion, a record of poverty and inequality is left, thus determining the measure and distance of a society, since those who participate in a dynamic are benefited, and those who are excluded are ignored by this same society, in conclusion We would say that social exclusion is a manifestation and expression reflected in the result of a social structure